European perspective on multiple myeloma treatment strategies: Update following recent congresses - Ludwig, H.; Avet-Loiseau, H.; Bladé, J.; Boccadoro, M.; Cavenagh, J.; Cavo, M.; Davies, F.; De La Rubia, J.; Delimpasi, S.; Dimopoulos, M.; Drach, J.; Einsele, H.; et al. (Oncologist, 2012)
The management of multiple myeloma has undergone profound changes over the recent past as a result of advances in our understanding of the disease biology as well as improvements in treatment and supportive care strategies. Notably, recent years have seen a surge in studies incorporating the novel agents thalidomide, bortezomib, and lenalidomide into treatment for different disease stages and across different patient groups. This article presents an update to a previous review of European treatment practices and is based on discussions during an expert meeting that was convened to review novel agent data published or presented at medical meetings until the end of 2011 and to assess their impact on treatment strategies. ©AlphaMed Press.
Keywords: bortezomib; Lenalidomide; multiple myeloma; novel agents; Thalidomide